Pengaruh Social Media Marketing Dan Electronic Word Of Mouth Terhadap Loyalitas Pelanggan Di Senyum World Hotel - Muhammad Yusuf Hilmy; Yosi Afandi; Ita Rifiani Permatasari (Jurnal Ekonomi dan Bisnis Digital, 2025)
Hospitality companies often utilize loyalty programs to enhance value, brand image, and customer trust, leading to customer engagement, improved experiences, and positive WOM. The predominant method employed by Senyum World Hotel involves social media marketing, particularly on Instagram, by keeping customers updated on their products or services, aiming to retain customer loyalty. Hence, this study aims to investigate the influence of social media marketing and Electronic Word of mouth on customer loyalty at Senyum World Hotel.